Analysis of Employability Skill on Students of English Teacher Prospective - Wandi Syahfutra; Siti Niah; Novela Nur Afrezah Afrezah (Universitas Lancang Kuning, 2022)
This research aimed to determine the employability skills of English Education students at Universitas Muhammadiyah Riau. This research conducted because there are some students who do not have work competence, have not mastered ICT (Information and Communication Technology), have not been able to communicate in English well and think critically, less innovative, and have not been problem solving oriented. This study used a qualitative approach in data collection, while the data collection techniques used questionnaires, interviews, and documentation. The population and sample are English Education students in the even semester of 2021. The sampling technique used purposive sampling. Data analysis was carried out using qualitative descriptive analysis. The results of this study will be stated in the form of publications articles in the Sinta 2 Accredited National Journal in the field of English education. The article will be published in the journal Eralingua. In addition to accredited national journals, research results will be published in Scopus indexed international journals as additional outputs, namely the International Journal of Instruction and produce a Manuscript, and Copyright recorded by the Director General of Intellectual Property Rights, Ministry of Law and Human Rights.